KAJIAN PRA-KLINIS PEMBERIAN ORAL BUBUK KERING-BEKU SUSU KEDELAI YANG DIFERMENTASI OLEH Lactobacillus plantarum AP1 DAN Sphingobacterium SP. TB17 PADA TIKUS - Achmad Dinoto; Rita Dwi Rahayu; Sri Purwaningsih (The East Java Biological Society, 2011)
To investigate the effects of oral administration of freeze-dried soymilks fermented by Lactobacillus plantarum AP1 and Sphingobacterium sp. TB17, in preclinical study groups of male Sprague Dawley rats were fed for 3 weeks with four different test diets: basal diet (CD), basal diet supplemented with 3% (w/w feed) freeze-dried unfermented soymilk (CN), basal diet supplemented with 3% (w/w feed) freeze-dried soymilk fermented by L. plantarum AP1 (CL), and basal diet supplemented with 3% (w/w feed) freeze-dried soymilk fermented by Sphingobacterium sp. TB17 (CK). Our result showed a reduction of serum cholesterol level up to 15% in rats CB after three weeks consuming soymilk fermented by L. plantarum AP1. This yield was relatively higher than that of rats CK consuming soymilk fermented by Sphingobacterium sp. TB17 to reduce serum cholesterol only up to 5%. Although unfermented soymilk (CN) also showed the hypocholesterolomic effect to rats, the reduction of cholesterol serum level was lower than that of rat CL. There were no signifi cant increased in blood glucose and body weight of rats as impact of freeze-dried fermented soymilk. Interestingly, although feed intake tends to increase during fermented soymilk consumption, the body weight of rats did not increase. In general, this study indicated that L. plantarum AP1 soymilk is a promising beneficial food product for the health.